Combined Phacoendoscopic Cyclophotocoagulation versus Combined Phacotrabeculectomy in the Management of Coexisting Cataract and Glaucoma: A Comparative Study - Charles Sing Lok Lau; Jeffrey Chi Wang Chan; Sophia Fei So; Orlando Chia Chieh Chan; Kenneth Kai Wang Li (Journal of Ophthalmology)
Purpose. To compare the surgical outcome of combined phacoemulsification and endoscopic cyclophotocoagulation (phacoECP) versus combined phacoemulsification and mitomycin C-augmented trabeculectomy (phacoTbx) in patients with coexisting glaucoma and visually significant cataract. Methods. A retrospective review of 89 eyes of 89 patients who received phacoECP (N=49) and phacoTbx (N=40) was carried out at a tertiary eye center in Hong Kong. The minimum follow-up period was 6 months. Criterion of success was reduction of IOP at least 30% or absolute IOP of 15 mmHg or below without (complete success) or with (qualified success) antiglaucomatous medication. Results. PhacoTbx had more reduction of antiglaucomatous medication (4 vs 1, P<0.001). At postoperative year one, there was more IOP reduction for phacoTbx than phacoECP (8 mmHg vs 3 mmHg, P=0.012). The one-year complete success rate was also higher for phacoTbx (46.2% vs 8.2%, P<0.001), while qualified success was comparable between the 2 groups (74.4% vs 73.5%, P=0.925). Operation time was shorter for phacoECP (37 vs 73 minutes, P<0.001). The number of postoperative follow-up visits was less (6 vs 11.5, P<0.001) for phacoECP. Additional surgical procedures were more common in phacoTbx (55% vs 0%, P<0.001). There was no postoperative cystoid macula edema, hypotony, or endophthalmitis reported in both groups. Conclusions. PhacoECP is significantly less effective than phacoTbx in reduction of both IOP and number of antiglaucomatous medications for patients with medically uncontrolled glaucoma and cataract. Its complete success rate is also significantly lower than that of phacoTbx. With its comparable qualified success, shorter operation time, less number of postoperative visits, and secondary surgical intervention, phacoECP may still have a role in very selected cases.